Everyday things change: Australian athlete communication during the Coronavirus lockdown - Whales, L.; Frawley, S.; Cohen, A.; Nikolova, N. (International Journal of Sport Communication, 2020)
During the coronavirus (COVID-19) pandemic, Australian professional sport leagues were impacted by temporary league shutdowns. One example is the Suncorp Super Netball, the world`s premier netball competition. This commentary paper explores the Suncorp Super Netball league shutdown from the perspective of the players. Our commentary has emerged from an ongoing ethnographic study supported by interviews with two players (a representative on the players association and a club captain) conducted during the league shutdown. Such a shutdown was the first in the history of the league, and it required an unprecedented response, coordinated by interdependent stakeholders. The authors outlined the importance of stakeholder communication in effectively navigating this extraordinary situation. In addition, the authors discussed the usefulness of technology-as-context for teamwork and leadership, given the limitations on physical interaction and geographical separation. In conclusion, the authors proposed recommendations for sport practitioners and potential research directions resulting from the coronavirus-related league shutdown.